Islam and Human Rights: Friend or Foe? - Abshar, Fariz Ulul; Khanif, Al; Efendi, A'an; Muktafi, Muktafi (LPPM IAIN Kudus, 2021)
In the context of the relationship between Islam and democracy along with human rights, Islam represents two opposing positions (the two faces of Islam). On the one hand, Islam is seen as a religion of compassion (raḥmat li al-‘ālamīn), respects plurality, upholds tolerance and cares about human rights. On the other hand, Islam is often identified with separatism, discrimination, intolerance and violent phenomena. In Islamic countries and Muslim-majority countries, violations of human rights frequently occur. Islam often appears with a double face. In addition to being a source of law to bring about peace, it is often used as the basis for violent ideologies from state’s repressive policies to terrorism movements. This article elaborates on the basic concept of human rights in Islam and the dynamics of protecting and upholding human rights. Using a conceptual approach, this study aims to seek religious awareness in the midst of globalization where religion can strengthen the concepts of human rights. When religion is used as a source in the rational policy framework of a country, especially the protection and enforcement of human rights, it can be ascertained that human rights in that country will flourish and will be accepted by the citizens.